Molarity model of mass transfer process for extraction in rotating disc contractor column [electronic resource] - Nurul Nadiya Abu Hassan, 1987- (2011)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2011